Improvement of the Power System's Transient Stability Using the Unified Power Flow Controller with Fuzzy Logic Technique - Raghad Hameed Ahmed; Ahmed Said Nouri (Journal of Techniques)
By combining the functions of many FACTS (flexible alternative current transmission systems) devices into a single unit, the UPFC (unified power flow controller) is the most efficient FACTS device available. Two voltage converters work together to form the Unified Power Flow Controller, a flexible tool for enhancing voltage regulation, power flow management, and power system stability. Both converters rely heavily on their control methods. This article discusses the power flow mechanism in a transmission line, which is necessary for understanding the functioning of UPFC in a transmission line and using a standard PI controller with voltage references in the control circuit of both converters. This study aims to enhance the power system's dependability and stability by developing a smart support-based UPFC device. Fuzzy logic is a useful tool for controlling UPFC equipment in a variety of failure scenarios. The fuzzy logic controller contrasts power grid characteristics such as a rotor speed deviation to a reference value to create operational pulses for the voltage source converter in the UPFC system. The suggested model will be tested using MATLAB simulation. The success of the proposed model is shown by thoroughly comparing simulation results to those of previously established models. This research paper's original contribution is the creation of a smart support-based UPFC device with fuzzy logic control. By comparing power system parameters such as rotor speed deviation to a reference value and generating operational pulses for the voltage source converter in the UPFC system, this technique increases the electricity grid's dependability and stability. The effectiveness of the suggested model is proved by a comparison of simulation results obtained in a MATLAB environment with those obtained from previously developed models.